Enhanced Service-Oriented Open Sensor Web Architecture with Application Server Based Mashup - Muhammad Sohail Khan; DoHyeun Kim (International Journal of Distributed Sensor Networks)
Connecting the sensing devices present in the physical world to detect and measure various physical phenomenon such as temperature, humidity, and pollution into a network and presenting them as web resources to the end users have become the goal of a variety of research activities. As the physical network of these devices inherently possesses a heterogeneous nature thus most of the sensor web studies are based on providing domain specific solutions. Service-oriented architecture (SOA) has proven successes to resolve the scalability and evolvability of the web. The present solutions for the SOA based sensor web allows the users to access the sensor data as services but to integrate these services the client must put extra effort to implement the logic. We present an improved SOA based sensor web architecture which offers an easy approach to integrate sensor providers’ services with information provider services and enable the users to access it as a single, integrated, and searchable service. This approach offers the functionality present in the existing solutions as well as an integrated data access or service mashup. We discuss in detail an instance architecture for indoor environment monitoring, based on the proposition of this study.